2016
DOI: 10.1128/jvi.01346-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues That Affect Oligomerization and/or Enzymatic Activity of Influenza Virus H5N1 Neuraminidase Proteins

Abstract: Influenza A virus (IAV) attachment to and release from sialoside receptors is determined by the balance between hemagglutinin (HA) and neuraminidase (NA). The molecular determinants that mediate the specificity and activity of NA are still poorly understood. In this study, we aimed to design the optimal recombinant soluble NA protein to identify residues that affect NA enzymatic activity. To this end, recombinant soluble versions of four different NA proteins from H5N1 viruses were compared with their full-len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 51 publications
4
52
0
Order By: Relevance
“…Analysis of the relative specific activities of the different proteins when the MUNANA substrate was used indicated that the HN, TK, and HB proteins cleave this substrate 2to 3-fold more efficiently than the VN protein ( Fig. 1A), in agreement with previous results (22). A remarkably different result was obtained when the relative specific activity was determined with fetuin using ECA staining ( Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Analysis of the relative specific activities of the different proteins when the MUNANA substrate was used indicated that the HN, TK, and HB proteins cleave this substrate 2to 3-fold more efficiently than the VN protein ( Fig. 1A), in agreement with previous results (22). A remarkably different result was obtained when the relative specific activity was determined with fetuin using ECA staining ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…Previously, we expressed recombinant soluble tetrameric versions of the N1 proteins derived from different highly pathogenic H5N1 viruses (A/duck/Hunan/795/2002, A/Vietnam/1194/04, A/turkey/Turkey/1/2005, and A/Hubei/1/2010, referred to as HN, VN, TK and HB viruses, respectively) and analyzed their enzymatic activities using the monovalent substrate MUNANA [2=-(4-methylumbelliferyl)-␣-D-N-acetylneuraminic acid] (22). In the current study, we analyzed the enzymatic activity of these proteins by enzyme-linked lectin assays (ELLAs) (10) using the glycoproteins fetuin and transferrin.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we compared the HA receptor-binding properties of a novel H7N9 virus isolated from a human patient in 2013 (A/Anhui/1/2013, referred to as "Anhui") with those of a closely related avian H7N9 virus from 2008 (A/Anas crecca/Spain/1460/ 2008, referred to as "Spain") (15). However, the NA stalk domain may contribute to correct folding (30) and affect enzymatic activity (31,32). Detailed analysis of the N9 proteins was precluded, however, by the low expression levels and activities of the recombinant soluble N9 proteins.…”
Section: Resultsmentioning
confidence: 99%
“…1A). We previously showed that replacing GCN4-pLI with a tetrabrachion tetramerization domain also resulted in NA proteins with higher specific activity (31), and therefore, we made N9 constructs with such a tetrabrachion domain. Therefore, we constructed novel expression vectors encoding N9 protein head domains extended with their stalk sequences ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation